Substrate turnover after injury. - Frayn, K (1985)
This review is concerned with turnover of plasma 'energy substrates' - principally glucose, fatty acids and ketone bodies - after injury and in sepsis. In both states, there is an initial mobilization of fuel stores followed, in severe conditions, by a 'shock phase' in which there are inhibitory effects on metabolism, particularly that of carbohydrate. The later responses to injury and chronic sepsis, characterized by increased metabolic rate and urinary nitrogen excretion, involve increased turnover and oxidation of both carbohydrate and fat. While the wound itself may contribute to this hypermetabolic state after injury, these changes appear mainly to reflect a coordinated whole-body response. In both chronic sepsis and injury there is an abnormal response to glucose infusion, with an apparent impairment of glucose oxidation relative to that of fat.